The effects of utilizing smartphone in enhancing students' English writing skills in Pakistan - Siddique, Muhammad (2017)
Though mobile learning offers myriad language learning opportunities to digitally smart learners, yet Pakistani lecturers are still utilizing conventional pedagogical methods to teach English writing skills. The objective of this 8-week study was to investigate the effects of smartphone in enhancing students’ English writing skills in Pakistan. To conduct this mixed method study, purposive sampling was employed to choose 45 intermediate students as participants. The pre-test/post-test, questionnaire on motivation and semi-structured interviews were used for data collection. In addition, the study investigated the views of the one lecturer and four students regarding the effects of utilizing smartphone as a teaching and learning tool. The quantitative data was analyzed by applying Paired-samples t-test employing SPSS (Windows version 24.0). However, the qualitative data was analyzed and interpreted holistically based on the emerging themes. The key findings from the Paired-samples t-test indicated that the students significantly scored higher (after intervention utilizing smartphones) on their overall mean scores not only for the descriptive essay and its eight components but also for motivation. Similarly, the qualitative findings revealed that smartphone played an effective role that motivated the students to enhance their writing skills by engaging them in a fun learning and student-centered environment. Based on the findings, it is recommended that future studies should use smartphones to address other genres of writing with female samples from other provinces of Pakistan. Moreover, the findings support the theories such as multimedia, mobile learning, cooperative learning, process approach and theory of motivation. Besides, the curriculum designers should promote the utilization of smartphones to address issues in writing skills.